Analysis of The Performance of ‎Sustainability Indices Compared to ‎Thematic Indices in ‎The Indian Stock Market - Nirban , Jyoti; Bhardwaj , Dr. Indira (International Journal of Accounting and Economics Studies, 2025)
The growing global focus on sustainability has led to the development of sustainability ‎indices, which evaluate companies based on environmental, social, and governance (ESG) ‎criteria. At the same time, thematic indices, which concentrate on specific investment themes ‎such as technology, infrastructure, or renewable energy, have gained popularity among ‎investors. This study investigates the performance of sustainability indices compared to ‎thematic indices within the Indian stock market. ‎ By utilizing historical data, risk-return metrics, and econometric models, this research assesses ‎whether sustainability indices deliver superior financial performance, lower volatility, or ‎improved risk-adjusted returns in comparison to thematic indices. The findings of this ‎research aim to provide valuable insights for investors, policymakers, and financial analysts on ‎the trade-offs between sustainable investing and thematic investing in India‎.